Suicidality and substance abuse in Turkish youth - Parna Prajapati; Ali Unlu; Andres Pumariega (Academia Mental Health & Well-Being)
Objective: To examine the types of substance use associated with suicidal ideation based on age group, gender, and school type in a sample of Turkish youth. Methods: The study data were collected by the Istanbul Department of Education on 31,604 high school (HS) students who received a 66-question survey that was administered in the school setting. The sample consisted of 53% female and 46.3% male participants, with an age range of 13–21 years. The survey sub-questions were added to generate new independent variables used to examine the relationship between substance use and suicidal ideation based on age, gender, and school type. Binary logistic regression was run between the dependent variable (suicidal ideation) and independent variables (type of substance use) based on three models: age, gender, and type of school. The standardized coefficients were calculated with a p-value of 0.05 and odds ratios were reported. Results: The use of tobacco and sleeping pill was significantly associated with suicidal ideation among all age groups, and in both gender participants and those in regular and vocational schools. Ecstasy was significantly associated with suicidal ideation among older age groups and Anatolian school participants. Substance use among vocational school participants and those who were in older age groups had a significant association with suicidal ideation. Conclusions: A pattern of substance use was seen in this study, specifically highlighting the need for educational and other preventive measures among Turkish youth, with greater emphasis on youth in older age groups and vocational HSs.